2019
DOI: 10.1128/mra.00410-19
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Massilia sp. Strain MC02, Isolated from a Sandy Loam Maize Soil

Abstract: From farmed corn soil in California, we isolated and sequenced a new member of the genus Massilia, Massilia sp. strain MC02. Massilia sp. MC02 has an assembled draft genome of 5,023,356 bp with a total of 4,790 protein-encoding genes and 3,028 predicted proteins, 47 tRNA genes, and 2 rRNA operons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Subsequent emergence of small unlabeled (or partially labeled) fractions of Glucn and 2KGlucn, notably in the oxic incubation and to a lesser extent in the anoxic incubation, is in accordance with priming effect of the glucose pulse to induce the oxidation of unlabeled glucose possibly derived from de novo breakdown of carbohydrate polymers in the soil. Of relevance to the above findings, previous genomics-based profiling studies of soil microbial response to glucose input under both oxic and anoxic conditions have reported increased populations of several bacterial genera (Arthrobacter, Pseudomonas, Acinetobacter, Massilia, Flavobacterium, Bacillus, Enterobacteriaceae), ,, all of which possess the glucose dehydrogenase and gluconate 2-dehydrogenase genes encoding the enzymes responsible for the production of Glucn and 2KGlucn, respectively. ,, …”
Section: Resultsmentioning
confidence: 66%
“…Subsequent emergence of small unlabeled (or partially labeled) fractions of Glucn and 2KGlucn, notably in the oxic incubation and to a lesser extent in the anoxic incubation, is in accordance with priming effect of the glucose pulse to induce the oxidation of unlabeled glucose possibly derived from de novo breakdown of carbohydrate polymers in the soil. Of relevance to the above findings, previous genomics-based profiling studies of soil microbial response to glucose input under both oxic and anoxic conditions have reported increased populations of several bacterial genera (Arthrobacter, Pseudomonas, Acinetobacter, Massilia, Flavobacterium, Bacillus, Enterobacteriaceae), ,, all of which possess the glucose dehydrogenase and gluconate 2-dehydrogenase genes encoding the enzymes responsible for the production of Glucn and 2KGlucn, respectively. ,, …”
Section: Resultsmentioning
confidence: 66%
“…accession no. VLKW00000000) (37); however, otherwise, the Massilia strains of this study show a larger size (average 7.0 Mbp) than Massilia genomes so far reported in the literature (average, 5.6 Mbp) (23)(24)(25)(26)(27)(28)(29). Each of the six strains carried one circular chromosome, and in the strain M. dura DSM 17513 T , one additional extrachromosomal circular replicon, 38.9 kbp in size, was identified by in silico prediction.…”
mentioning
confidence: 50%
“…It was reported Pseudomonas could help the plant to produce osmoreceptors (proline, choline, and glycine betaine), and photosynthetic pigments and reduced the production of MDA contents to mitigate the adverse effects of the moisture stress ( Yasmin et al, 2022 ). Azoarcus has the ability to dissolve inorganic phosphate ( Fernández-Llamosas et al, 2021 ), whereas Massilia is known to be rich in the plant rhizosphere and is involved in the soil carbon cycle, particularly in the colonization of roots ( Raths et al, 2019 ). Krishnamoorthy et al found that the combined application of Massilia and arbuscular mycorrhizal fungi alleviated the effects of salt stress on plant growth, root colonization, nutrient accumulation and growth ( Krishnamoorthy et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%